2016
DOI: 10.1073/pnas.1600070113
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of trimethylated H3K27 regulated by polycomb protein EED is required for embryogenesis, hematopoietic maintenance, and tumor suppression

Abstract: Polycomb repressive complex 2 (PRC2) catalyzes the monomethylation, dimethylation, and trimethylation of histone H3 Lys27 (H3K27) and acts as a central epigenetic regulator that marks the repressive chromatin domain. Embryonic ectoderm development (EED), an essential component of PRC2, interacts with trimethylated H3K27 (H3K27me3) through the aromatic cage structure composed of its three aromatic amino acids, Phe97, Trp364, and Tyr365. This interaction allosterically activates the histone methyltransferase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…13A), deletions, amplifications, and translocations in chromatin-modifying enzymes, including those in different subunits of PRC2 are found in various types of human cancer. For example, nonsense and inactivating mutations in EED or SUZ12 are found in 70%-90% of malignant peripheral nerve sheath tumors (MPNSTs); in EZH2, EED, or SUZ12 in 25% of T-cell acute lymphoblastic leukemia (T-ALL) (Ntziachristos et al 2012;Lee et al 2014); and in PRC2 core subunits in other cancer types with lower frequencies, such as myelodysplastic syndrome (MDS) and other myeloid malignancies (Sashida et al 2014;Ueda et al 2016). Although the functions of many other sense mutations in core PRC2 subunits remain undetermined, most of them are likely to be loss of function, as mutations tend to be deleterious rather than to evolve new functions.…”
Section: Dysregulation Of Prc2 In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…13A), deletions, amplifications, and translocations in chromatin-modifying enzymes, including those in different subunits of PRC2 are found in various types of human cancer. For example, nonsense and inactivating mutations in EED or SUZ12 are found in 70%-90% of malignant peripheral nerve sheath tumors (MPNSTs); in EZH2, EED, or SUZ12 in 25% of T-cell acute lymphoblastic leukemia (T-ALL) (Ntziachristos et al 2012;Lee et al 2014); and in PRC2 core subunits in other cancer types with lower frequencies, such as myelodysplastic syndrome (MDS) and other myeloid malignancies (Sashida et al 2014;Ueda et al 2016). Although the functions of many other sense mutations in core PRC2 subunits remain undetermined, most of them are likely to be loss of function, as mutations tend to be deleterious rather than to evolve new functions.…”
Section: Dysregulation Of Prc2 In Cancermentioning
confidence: 99%
“…However, most evidence relies on EZH2 immunoprecipitation results, and it remains unclear whether such interactions are actually stable or Major groups of mutations that influence PRC2 function in cancer. Mutations that are found in the EED cage (EED I363M) (Ueda et al 2016) and SRM domain of EZH2 (P132S, D142V, and F145L) inhibit allosteric activation of PRC2 (Lee et al 2018c). Mutations that are found in the catalytic SET domain (Y646X [X = S, N, F, C, or H], A682G, A682V, and A692V) are gain-of-function "kinetic" mutations.…”
Section: Dysregulation Of Prc2 In Cancermentioning
confidence: 99%
“…[24][25][26][27] Among the integration sites detected, we identified 3 common integration sites (CISs): Mecom (Mds1 and Evi1 complex locus, also known as Evi1, ecotropic virus integration site 1), 28 Sfpi-1 (spleen focus forming virus proviral integration oncogene, also known as PU.1), 29 and Rassf2 (Ras association [RalGDS/AF-6] domain family member 2) 30 (supplemental Table 2). Examination of the expressional alteration of these genes in Cbl Q367P 1 MOL4070A and Cbl Q367P 1 ENU tumor tissues revealed that, although the expression levels of Rassf2 and Sfpi-1 were not apparently increased, that of Mecom/Evi1 was upregulated more than fivefold in 3 tumors (no.…”
mentioning
confidence: 99%
“…It seems that lower EED mRNA level could increase the metastasis and invasion potential of APL cancer cells. Viewed together with this hypothesis, we found that haploinsufficiency of EED gene in mouse caused by conditional deletion or mutant knockin could also increase the metastasis and invasion risk of leukemia cells (Ikeda et al 2016;Ueda et al 2016).…”
Section: Eed Mrna Level Were Associated With Laml Risk and Prognosismentioning
confidence: 74%